To simplify the product, we first need to multiply each term of the first expression (5y+2) by each term of the second expression (2y^2+y-4) using the distributive property.
First, let's multiply each term of the first expression by the second expression:
5y * 2y^2 = 10y^3
5y * y = 5y^2
5y * -4 = -20y
2 * 2y^2 = 4y^2
2 * y = 2y
2 * -4 = -8
Now, let's combine these results:
10y^3 + 5y^2 - 20y + 4y^2 + 2y - 8
Combine like terms:
10y^3 + 5y^2 + 4y^2 - 20y + 2y - 8
10y^3 + 9y^2 - 18y - 8
Therefore, the simplified product of (5y+2)(2y^2+y-4) is 10y^3 + 9y^2 - 18y - 8.
Simplify the product. Help Video HERE (5y+2)(2y2+y−4) (1 point)
1 answer